2020
DOI: 10.3389/fimmu.2020.598877
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Anticancer Immunity Through Combined Targeting of Angiogenic and PD-1/PD-L1 Pathways: Challenges and Opportunities

Abstract: studies. We also discuss data from recently reported randomized clinical trials. Finally, we discuss how these concepts and approaches can be further incorporated into clinical practice to improve immunotherapy outcomes for patients with cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
154
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(156 citation statements)
references
References 222 publications
2
154
0
Order By: Relevance
“…However, two years after its approval by the US Food and Drug Administration for metastatic BC, Bevacizumab was retracted due to an insufficient benefit/risk balance. It has been shown that Bevacizumab leads to a reduction of Treg in a CRC mouse model and in patients suffering from CRC [ 24 , 76 , 77 , 78 ] and increases the number of DCs in the peripheral blood [ 24 , 77 , 79 ]. Accordingly, Bevacizumab also reestablishes the ability of monocyte to differentiate into DC and restores the expression of CD86 and HLA-DR on DCs [ 65 ].…”
Section: A Whole Range Of Anti-vegf/vegfr Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, two years after its approval by the US Food and Drug Administration for metastatic BC, Bevacizumab was retracted due to an insufficient benefit/risk balance. It has been shown that Bevacizumab leads to a reduction of Treg in a CRC mouse model and in patients suffering from CRC [ 24 , 76 , 77 , 78 ] and increases the number of DCs in the peripheral blood [ 24 , 77 , 79 ]. Accordingly, Bevacizumab also reestablishes the ability of monocyte to differentiate into DC and restores the expression of CD86 and HLA-DR on DCs [ 65 ].…”
Section: A Whole Range Of Anti-vegf/vegfr Therapiesmentioning
confidence: 99%
“…Ramucirumab increases CD8 + T cell infiltration in the TME [ 83 ]. Ramucirumab [ 83 ] and Bevacizumab [ 24 , 76 , 77 , 78 ] reduce the frequency of Treg in the TME.…”
Section: A Whole Range Of Anti-vegf/vegfr Therapiesmentioning
confidence: 99%
“…By now, a number of randomized trials have shown remarkable results which have led to approvals by the FDA and/or EMA in renal cell carcinoma (axitinib plus pembrolizumab, and axitinib plus avelumab), endometrial carcinoma (pembrolizumab plus lenvatinib), non-squamous NSCLC (bevacizumab and atezolizumab), and hepatocellular carcinoma (bevacizumab plus atezolizumab). This broad clinical activity suggest that a combination strategy may also be of benefit in colorectal cancer [ 84 ].…”
Section: Anti-angiogenesis and Immunotherapymentioning
confidence: 99%
“…Increasing evidence suggests that antiangiogenic agents stimulate the immune system, and that immunotherapy might also exhibit antiangiogenic effects. It has been shown that VEGF weakens the antitumor immune response through two main modes of action: first, VEGF was shown to block the infiltration of T cells into the tumor by inhibiting the adhesion of lymphocytes to activated endothelial cells; and second, VEGF was shown to promote the function of immunomodulatory cells through a variety of mechanisms ( 72 ). Considering the immunosuppressive and angiogenic effects of VEGF in tumors, it is not surprising that antiangiogenic agents stimulate the immune response and enhance the effectiveness of immunotherapy.…”
Section: Therapeutic Strategies For Different Tumor Types In His Micementioning
confidence: 99%